Plate-Assisted Intramedullary Nailing of Proximal Third Tibia Fractures. Issue 6 (June 2020) - Cinats, David J.; Perey, Bertrand; Moola, Farhad; Boyer, Dory; Lemke, Helmut M.; Stone, Trevor; Apostle, Kelly; Viskontas, Darius
Abstract : Objectives: To report on the safety of unicortical plate stabilization in conjunction with intramedullary nailing (IMN) of proximal third tibia fractures. Design: Retrospective cohort. Setting: A Level I trauma center. Patients/Participants: All Orthopaedic Trauma Association 41A and 42A/B/C proximal tibia fractures treated with IMN from January 2011 to May 2018 were reviewed. Fifty-three proximal tibia fractures in 50 patients were included in the study. Twenty-four patients were treated with plate-assisted reduction and IMN, and 29 were treated with IMN alone. The plate-assisted IMN cohort was subdivided into patients with plate retention and those that had the plate removed. Intervention: Plate-assisted IMN and IMN only. Main Outcome Measurements: Patients were followed up for evidence of nonunion, reduction quality, postoperative infection, and rate of implant removal. Results: There were no statistically significant differences between plate-assisted IMN and IMN only for age, fracture type, mechanism of injury, quality of reduction, or implant removal rate. Open fractures were treated more often with plate-assisted IMN (88%) compared with the number of open fractures treated with IMN only (12%). There were no differences in nonunion rate or rate of postoperative infection between the 2 groups. Conclusions: Plate-assisted IMN of proximal third tibia fractures can safely be performed even in open tibia fractures with similar rates of nonunion, infection, and implant removal rates to patients treated with IMN only. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.